Spiral toolpath definition and G-code generation for single point incremental forming / Zeradam Yeshiwas and A. Krishniah - Yeshiwas, Zeradam; A., Krishniah (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2020)
The research to date has not been able to confirm earlier findings showing the commercial availability of the tool path definition package for Single Point Incremental Forming (SPIF). There has been substantial research undertaken on the tool-path definition for SPIF by using CAM package or Matlab script. However, the coordinate points from Matlab must get changed to G-code to introduce in the CNC mill. Previous studies on SPIF have not dealt with the conversion of Matlab script into G-code. In the current study, a methodology has been proposed to convert the tool path trajectories generated using Matlab script into G-code. Three different shapes i.e. the truncated cone, pyramid, and hyperbola were chosen for the definition of tool-path trajectory. The method was tested using Simco edit software and successfully working. This study fills a gap in the literature by introducing a method to convert Matlab script into G-code.